Assessing the hydrologic impacts of military maneuvers - Pugh, Ginger E. (Kansas State University, 2013)
Military land management is vital to the future health and usability of maneuver training areas. As land disturbance increases, runoff from the area also increases and may create significant erosion potential. Determining the relationship between what is safe training versus what is harmful to the environment can be done by determining runoff potential at different disturbance percentages given different training intensities. Various studies have shown that soil density, soil structure, plant biodiversity, animal biodiversity, and many other essential ecosystem factors are greatly damaged by continuous training. These ecosystem factors influence runoff amounts and likewise erosion potential in that area. The primary factor examined in this study was the Curve Number (CN). Since military procedures do not have predefined CNs, representative CNs were created based off of CNs for agricultural use and supplemental research about training impacts on the land. Training intensity was broken into four classes: undisturbed, light use, moderate use, and heavy use. Five sample watersheds on Fort Riley were used as replications for the study. Disturbance intensity indexes were broken into 10% increments, and changes in runoff amount and peak rate modeled with TR-55. Statistical analysis was done comparing watersheds, training intensities and disturbance percentages for different storm magnitudes to assess statistically significance of changes in runoff amount and peak rate. This analysis showed that runoff amount and rate were both significantly impacted at every 10% increase on disturbance percentage. Results also showed that at the lower disturbance percentage (less than 30%), runoff amount and rate were not significantly impacted by training use classes. From this it can be seen that even with very little training done to the land increased erosion can be expected.
Keywords: Runoff; Hydrologic modeling; Military maneuvers; Fort Riley; Environmental Engineering (0775)